Challenges and opportunities in implementing and enforcing India's loose cigarette sales ban: A qualitative stakeholder analysis. - Mayank Sakhuja; Daniela B Friedman; Mark M Macauda; James R Hebert; Mangesh S Pednekar; Prakash C Gupta; James F Thrasher (PLoS ONE)
Introduction Several Indian states have banned the sale of loose cigarettes, and India is considering a national ban. This study examines the perceptions of policymakers, implementers, and law enforcement officials regarding the implementation and enforcement of this ban. Methods Between May-October 2022, we conducted in-depth interviews with 26 key stakeholders involved in tobacco control in two Indian cities, Delhi (where the ban was not implemented) and Mumbai (where the ban was in effect). Participants included representatives from various government departments such as police, municipal corporations, FDA, health, and civil society organizations / NGOs such as Vital Strategies, World Health Organization, International Union against Tuberculosis and Lung Disease, and local NGOs. Interviews explored policy awareness, implementation and enforcement status, and factors influencing implementation and enforcement of the ban. Interview transcripts were organized in NVivo, and reflexive thematic analysis was conducted. Results In Mumbai, awareness of the ban was poor among implementers and law enforcers, including FDA, municipal, and police officials, while it was higher among health department officials and NGOs directly involved in tobacco control. Participants from Mumbai expressed that the implementation and enforcement of the ban was poor and loose cigarettes were still widely available. Main barriers to policy implementation included unclear implementation guidelines, poor awareness among tobacco vendors, limited resources, and lack of stakeholder commitment for tobacco control. Participants from both the cities emphasized the need for a vendor licensing system, imposing hefty penalties, imparting health education, and a multi-sectoral approach for effective policy implementation and enforcement. Conclusion Limited awareness of the ban and continued sale of loose cigarettes highlight gaps in policy implementation and enforcement. Effective policy implementation and enforcement requires raising awareness regarding the policy, adopting a tobacco vendor licensing system, and establishing clear implementation guidelines involving a multi-sectoral approach.